The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.2319/121308-632r.1
|View full text |Cite
|
Sign up to set email alerts
|

Pain and Orthodontic Treatment

Abstract: Objective: To explore whether patients' pain experiences and orthodontists' assessments of their patients' pain levels are consistent and whether orthodontists are aware of their patients' use of pain medication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
65
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(77 citation statements)
references
References 22 publications
5
65
0
1
Order By: Relevance
“…17 Hence, the objectives of this project were to modify and validate the MPQ-SF for assessment of the nature, quality, and intensity of pain experienced by adolescent orthodontic patients.…”
Section: Introductionmentioning
confidence: 99%
“…17 Hence, the objectives of this project were to modify and validate the MPQ-SF for assessment of the nature, quality, and intensity of pain experienced by adolescent orthodontic patients.…”
Section: Introductionmentioning
confidence: 99%
“…Pain affects both quality of life and treatment cooperation 26. The feeling of pain is considered a subjective parameter 18.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas some studies suggested that there is no correlation between gender and pain, some claimed there is a connection between them. 4,11,21,22 Therefore, though the numbers of boys and girls were close, we did not discriminate the gender of the patients. All of our patients had heavy archwires.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, the relationship between what patients felt and how the clinicians evaluated these pain experiences was investigated, and it was reported that the clinicians frequently tend to underestimate the patient's suffering. 21 The aim of this study was to determine the pain levels of the patients during the use of intermaxillary elastics.…”
Section: Discussionmentioning
confidence: 99%